Chlorhexidine-induced anaphylaxis occurring in the workplace in a health-care worker: case report and review of the literature - Toletone, Alessandra; Dini, Guglielmo; Massa, Emanuela; Bragazzi, Nicola Luigi; Pignatti, Patrizia; Voltolini, Susanna; Durando, Paolo (La Medicina del Lavoro, 2018)
Background: Chlorhexidine has been widely used in the occupational field as an effective antiseptic and disinfectant, especially in the health-care services. Several cases of allergic reactions to chlorhexidine have been reported, both in the general population and in workers. Objectives: To describe a case of occupational chlorhexidine-induced severe anaphylaxis that occurred in the workplace in a health-care worker (HCW) and to update the literature on chlorhexidine as a possible occupational allergen. Methods: We report a case of a severe anaphylactic reaction that occurred in the workplace in a 63-year-old man, who had worked as a dentist for over 20 years. We also carried out a systematic review of the literature according to the PRISMA guidelines. No time or language filters were applied. Only occupational case-reports and case-series were included. Results: The causative role of chlorhexidine was suspected owing to the presence of chlorhexidine-containing products in the workplace. Positive results on the Basophil Activation Test confirmed the diagnosis of immediate chlorhexidine-induced hypersensitivity reaction and excluded a role of other disinfectants. No other causes of anaphylaxis were suspected. Our systematic literature review identified 14 cases of occupational chlorhexidine-induced allergy among HCWs; in these cases, the clinical presentation was mild and the symptoms resolved. No cases of systemic reactions in the workplace were reported. Conclusions: This is the first report of chlorhexidine-induced severe anaphylaxis occurring in the workplace. This case report underlines the importance of investigating and being aware of individual and environmental risk factors in the occupational field, which can cause, albeit infrequently, severe reactions with serious consequences.